2011
DOI: 10.1590/s0102-09352011000100006
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography in the diagnosis of steroidal hepatopathy in a dog: case report

Abstract: It is reported a case of an eight-year-old Yorkshire Terrier dog, with a history of prolonged use of prednisone in a dosage of 1mg/kg of body weight each 24 hours during two years. The helical computed tomography revealed hepatomegaly associated to a hyperattenuation of the parenchyma, with a radiodensity value of 82.55 Hounsfield units (HU). The spleen presented a mean radiodensity of 57.17HU, and a radiodensity difference of 25.38HU was observed between the two organs. Based on the history and findings of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The information regarding this type of liver pathology is limited to a few reports dealing with steroid hepatopathy in dogs [ 18 , 19 ] and hepatic lipidosis in cats [ 20 , 21 ]. The attenuation values of the canine liver with steroid hepatopathy were measured only in the pre-contrast CT examination, and were reported as hyperattenuating [ 18 , 19 ]. Steroid hepatopathy is characterized by glycogen accumulation in the liver parenchyma [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The information regarding this type of liver pathology is limited to a few reports dealing with steroid hepatopathy in dogs [ 18 , 19 ] and hepatic lipidosis in cats [ 20 , 21 ]. The attenuation values of the canine liver with steroid hepatopathy were measured only in the pre-contrast CT examination, and were reported as hyperattenuating [ 18 , 19 ]. Steroid hepatopathy is characterized by glycogen accumulation in the liver parenchyma [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of abdominal organs' radiodensity is widely performed in human patients (Leander et al, 2000;Tsujimoto et al, 2006, Kodama et al, 2007 and can be employed with high precision and reproducibility in animals, helping in the diagnosis of alterations in several organs (Ohlerth andSharf, 2007, Teixeira et al, 2007;Costa et al, 2010). A recent study demonstrated the occurrence of steroid hepatopathy in a dog subjected to prolonged corticosteroid therapy, with an increase of the parenchymal liver radiodensity (Costa et al, 2011). The aim of this study is to evaluate the possible alterations in radiodensity of the hepatic parenchyma and spleen resulting from the corticotherapy with prednisone, correlating these findings with serum biochemical hepatic transaminase activity.…”
mentioning
confidence: 96%